Circular and Sustainable Design : A systemic design model for the transition to a circular and sustainable economy - Camocho, David Geraldes; Vicente, José; Ferreira, Ana Margarida (My University, 2020)
Successful and innovative design practices towards the development of more circular and sustainable products and services that are aligned with the current and future needs of our society rely on efficient practices that combine three main levels in the design and development process. The design management level which is responsible for establishing, planning and managing the development of design projects. The business level, which is focused on the feasibility and effectiveness of the project and its results in the short and long term. Lastly, the design level that is responsible for the implementation and development of circular design projects. This paper is part of a PhD research focused on supporting an innovative and efficient transition to a circular economy and sustainability through design. It describes the basis of a design model under development based on the design thinking process and an expert's survey carried at an international level and the research activities undertaken. It integrates the three levels in a systemic perspective, guiding the process and establishing the link between the needs of the design and development teams in terms of the definition of circularity and sustainability considerations and strategies, objectives and the activities, resources and practical tools needed to support the circular design projects.
Keywords: Sustainability; Design systemic model; Circular Economy; Design